Resveratrol Modulates the Redox Response and Bile Acid Metabolism to Maintain the Cholesterol Homeostasis in Fish Megalobrama amblycephala Offered a High-Carbohydrate Diet - Yaping Ge; Ling Zhang; Weiliang Chen; Miao Sun; Wenbin Liu; Xiangfei Li (MDPI AG, 2023)
This study aimed to characterize the effects of resveratrol on the redox balance, cholesterol homeostasis and bile acid metabolism of Megalobrama amblycephala offered a high-carbohydrate diet. Fish (35.0 ± 0.15 g) were fed four diets including one control diet (32% nitrogen-free extract), one high-carbohydrate diet (45% nitrogen-free extract, HC), and the HC diet supplemented with different levels (0.04%, HCR1; 0.08%, HCR2) of resveratrol for 12 weeks. The HC diet-induced redox imbalance is characterized by increased MDA content and decreased T-SOD and CAT activities in the liver. Resveratrol attenuated this by up-regulating the transcription of Cu/Zn-sod, and increasing the activities of T-SOD, CAT, and GPX. The HC diet enhanced the cholesterol synthesis, but decreased the bile acid synthesis via up-regulating both hmgcr and acat2, and down-regulating cyp7a1, thus resulting in excessive cholesterol accumulation. Resveratrol supplement decreased cholesterol synthesis, and increased cholesterol uptake in the liver by down-regulating both hmgcr and acat2, and up-regulating ldlr. It also increased bile acid synthesis and biliary excretion by up-regulating cyp7a1, and down-regulating mrp2, oatp1, and oatp4 in the hindgut, thereby decreasing cholesterol accumulation. In conclusion, resveratrol improves the cholesterol homeostasis of Megalobrama amblycephala fed a high-carbohydrate diet by modulating the redox response and bile acid metabolism.